ستخدام طريقة هيبنوتيجينج لترقية دافع التلاميذ في تعلم اللغة العربية (بحث الفصل الإجرائي في الفصل الرابع بالمدرسة الابتدائية الاسلامية الاهلية نور الهدى سمبس) - alfia, yuni (Institut Agama Islam Negeri Pontianak, 2023)
The background of this research is the learning motivation of students which really needs to be improved. The aims of this study were: 1) to find out the motivation to learn Arabic in class IV MIS Nurul Huda Seburing students before using the Hypnoteaching method. 2) to find out the motivation to learn Arabic for class IV MIS Nurul Huda Seburing students after using the Hypnoteaching method. 3) to determine the level of effectiveness of the hypnoteaching method to increase the motivation to learn Arabic in class IV MIS Nurul Huda Seburing students. The type of research used is classroom action research (PTK). The research procedures used are: Planning, Implementation, Observation, Reflection. The sample in this study amounted to 33 students. Data collection techniques used in this study are: 1) Observation, 2) Questionnaire, and 3) Documentation. As well as data analysis used is quantitative research and quantitative research. The results of this study indicate an increase in student learning motivation as evidenced by the results of the questionnaire before using the hypnoteaching method of 66.66%, then there was an increase after using the hypnoteaching method in cycle I of 84.84%, and in cycle 2 of 90.90 %.